ATL. Issue 9 (1st November 2013) - Bjurberg, Maria; Brun, Eva
Abstract : Objective: The superiority of positron emission tomography (PET) with 2-deoxy-2-[18F]fluoro-D-glucose (FDG) over computed tomography and magnetic resonance imaging in detecting recurrent cervical cancer and determining the extent of the disease has been demonstrated in several clinical trials. However, there is a lack of data concerning the clinical impact of the extra findings. We report here a prospective clinical study aimed at investigating the clinical impact of FDG-PET findings on the treatment plans in recurrent cervical cancer. Materials and Methods: Thirty-six patients with suspected recurrent cervical cancer underwent FDG-PET. Relapses were confirmed in 26 cases, and one case of primary lung cancer was found. The clinical impact of the FDG-PET results was assessed using a systematic scoring system with a 4-grade scale. Median follow-up time after FDG-PET was 33.1 months (range, 5–83 months) for all patients and 22.4 months (range, 5–83 months) for patients with positive PET results. Results: More sites of metastases were detected with FDG-PET in 56% of the patients compared to the findings by conventional imaging. The results of FDG-PET led to a change in treatment modality for 33% of the patients; and for 22%, a change in dose or deliverance of treatment was recorded. Treatment intention was changed in 30%, in all but one patient, from curative to palliative. In 48% of the patients, the initially planned treatment was reduced regarding dose or extent, or was withheld. Conclusion: In recurrent cervical cancer, FDG-PET provides clinically valuable information with a high impact on treatment decisions.